Control design approaches for parallel robot manipulators: a review. (2017) - Azar, Ahmad Taher; Zhu, Quanmin; Khamis, Alaa; Zhao, Dongya
In this article, different control design approaches for parallel robot manipulators are presented with two distinguished classes of control strategies in the literature. These are the model-free control and the dynamic control strategy, which is mainly a model-based scheme, and is mostly the alternative when the control requirements are more stringent. The authors strongly believe that this paper will be helpful for researchers and engineers in the field of robotic systems.